2020
DOI: 10.1016/j.clnu.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Falls among older adults with sarcopenia dwelling in nursing home or community: A meta-analysis

Abstract: Objectives: To assess and quantify sarcopenia as a risk for falls among community-dwelling older people and nursing home older persons. Methods: Prospective cohort studies that evaluated the association between sarcopenia and falls in older adults were identified via a systematic literature search of Medline (via Ovid), PubMed, EMBASE, and the Cochrane CENTRAL Library from database inception until October 15, 2018, in English and Chinese. Results: 10 studies (10,073 participants) were included in the meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 46 publications
(43 reference statements)
2
92
0
3
Order By: Relevance
“…Furthermore, our study found that the prevalence of sarcopenia in breast cancer patients was 45% [95% CI: 32-57], which was higher than in community-dwelling older adults [32]. Considering this together with the results of previous studies substantiating that sarcopenia can increase the risk of negative clinical outcomes [33,34], it is recommended that assessment of sarcopenia should be incorporated as part of the routine clinical assessment for patients with breast cancer, particularly for those who are in the early stage. In addition, metastatic breast cancer patients usually receive chemotherapy or radiotherapy to increase their overall likelihood of survival.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, our study found that the prevalence of sarcopenia in breast cancer patients was 45% [95% CI: 32-57], which was higher than in community-dwelling older adults [32]. Considering this together with the results of previous studies substantiating that sarcopenia can increase the risk of negative clinical outcomes [33,34], it is recommended that assessment of sarcopenia should be incorporated as part of the routine clinical assessment for patients with breast cancer, particularly for those who are in the early stage. In addition, metastatic breast cancer patients usually receive chemotherapy or radiotherapy to increase their overall likelihood of survival.…”
Section: Discussionsupporting
confidence: 74%
“…Then, we chose the newest meta‐analysis with the largest number of studies. Finally, 54 health‐related outcomes extracted from 30 meta‐analyses 10,22‐50 were reported in this umbrella review. These 54 outcomes were mainly about prognostic outcomes of tumor, postoperative outcomes, age‐related outcomes, metabolic outcomes, and other outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…While literature regarding sarcopenia in orthopaedic-specific surgical procedures is sparse, our results are consistent with the literature, which include findings of increased fall risk in patients with sarcopenia. 6 Using data from the "Invecchiamento e Longevità nel Sirente" (Aging and Longevity in the Sirente geographic area, ilSIRENTE) study, Landi et al demonstrated that patients with sarcopenia were thrice more likely to experience falls (hazard ratio [HR] ¼ 3.23; 95% CI: 1.25-8.29). 8 In a 2-year prospective cohort study of 162 participants, Matsumoto et al found sarcopenia to be a predictor of falls in independently living older adults (OR ¼ 7.68; 95% CI: 1.41-41.77, p ¼ 0.018).…”
Section: Discussionmentioning
confidence: 99%